Comparison of geometric proof development tasks as set up in the textbook and as implemented by teachers in the classroom - Mwadzaangati, Lisnet (Pythagoras, 2019)

Use of Koha-integrated library system by higher education institutions in Malawi - Chaputula, Aubrey; Kanyundo, Allan (Digital Library Perspectives, 2019)
Purpose The purpose of this paper is to study the use of Koha integrated library system by higher education institutions in Malawi. Design/methodology/approach The study made use of the diffusion of innovation theory as an anchoring model. Data were collected using a survey questionnaire that was administered to library managers of higher education institutions registered with the National Council for Higher Education in Malawi. The data collected were analyzed using SPPS version 21 to generate descriptive statistics. Findings The findings revealed that 84.2 per cent of libraries in higher education institutions in Malawi are automated, and 81.3 per cent of them are using Koha ILS and the rest were using proprietary and other open source software. Cost and technical aspects have been discovered to be the primary factors that have assisted in the rapid diffusion of Koha. The study also exposed some factors that negatively impacted the use of Koha in the adopting institutions. The main ones included lack of information and communication technology infrastructure, unreliable Internet connectivity and limited finances. Originality/value Previously, some small-scale case studies have been performed to examine implementation of Koha in some higher education institutions in Malawi. However, this is the first large-scale attempt to investigate use of Koha among higher education institutions in the country. Findings that have shown that Koha can be installed easily and used at minimal cost could assist in its rapid adoption in the higher education institutions, a majority of whom face a myriad of financial challenges.
Keywords: _C:Malawi MWI

Synthesis of Reviews on Teacher Professional Development in Sub-Saharan Africa - Haßler, Björn; D’Angelo, Sophia; Walker, Hannah; Marsden, Melissa (Open Development & Education, 2019)
Keywords: Author:Haßler; AuthorFirst:Haßler; _bjoern_cv; _yl:i

Getting Started with the Mastery PD Materials - NCETM (2019)
This is "Getting Started with the Mastery PD Materials" by NCETM on Vimeo, the home for high quality videos and the people who love them.
Keywords: _C:United Kingdom GBR

An Exploration of Teaching for Understanding the Problem for Geometric Proof Development: The Case of Two Secondary School Mathematics Teachers - Mwadzaangati, Lisnet; Kazima, Mercy (African Journal of Research in Mathematics, Science and Technology Education, 2019)
Keywords: _C:Malawi MWI

The efficacy of peer education in sexual behavioral change among school-going adolescents in Northern Malawi: A quasi experiment - Mwale, Marisen; Muula, Adamson S. (Journal of HIV/AIDS & Social Services, 2019)
We conducted a quasi-experiment to investigate whether a peer education intervention could result in positive sexual behavioral change outcomes in selected schools in Northern Malawi. The experimental participants (n = 158) were exposed to an HIV risk reduction intervention. The control participants (n = 147) were exposed to a Health Promotion Package. At 8 months, there were significant improvements in the intervention arm on several outcomes. The experimental group was 96% less likely to have sex than the control (OR = 0.04, CI = 0.01–0.20). Intervention participants were also 3.49 times likely to report condom use when they had sex (OR = 3.49, 95% CI = 0.96 to 12.65) and had lower odds of having multiple sexual partners. There were no significant differences on abstinence and the desire to have medical male circumcision (MMC). We suggest the intervention has potential efficacy to improve HIV risk reduction among adolescents in Malawi and perhaps in other similar settings.Trial registration: Pan African Clinical Trial Registry identifier: PACTR201612001889209.
Keywords: Adolescent; HIV and AIDS; Malawi; _C:Malawi MWI; intervention; risk reduction

An Analysis of the Political Economy of Schooling in Rural Malawi: Interactions among Parents, Teachers, Students, Chiefs and Primary Education Advisors - Watkins, Susan; Ashforth, Adam (Research on Improving Systems of Education (RISE), 2019)
This study provides a rare ground-level picture of the interactions around schooling among parents, teachers, district-level brokers, as well as village chiefs in rural Malawi. Our primary objective is to provide insight into the everyday dynamics of village life surrounding issues of public primary schools and schooling in rural Malawi. Without understanding these dynamics, planning for systemic reform would be futile.
Keywords: _C:Malawi MWI; _important

Lesson Study in Mathematics: Current Status and Further Directions - Huang, Rongjin; Takahashi, Akihiko; Clivaz, Stéphane; Kazima, Mercy; INPRASITHA, MAITREE (2019)
Keywords: _C:Malawi MWI

‘These religions are no good – they’re nothing but idol worship’: mis/representation of religion in Religious Education at school in Malawi and Ghana - Matemba, Yonah; Addai-Mununkum, Richardson (British Journal of Religious Education, 2019)
Keywords: _C:Malawi MWI

Need and acceptability of story books intended to help with the process of informing children about their HIV status in Malawi: a mixed methods study - Kalembo, Fatch W; Kendall, Garth E; Ali, Mohammed; Chimwaza, Angela F (AIDS Care, 2019)
Keywords: _C:Malawi MWI

Malawi mathematics teacher educators’ understanding of Lesson Study - Fauskanger, Janne; Jakobsen, Arne; Kazima, Mercy (International Journal for Lesson and Learning Studies, 2019)
Purpose The purpose of this paper is to better understand the challenges involved in introducing Lesson Study (LS) into teacher education in Malawi by studying mathematics teacher educators’ (TEs’) understanding of planning for LS. Design/methodology/approach This study is a part of a wider ongoing project designed to improve the quality and capacity of mathematics teacher education in Malawi. One of its components is professional development of all mathematics TEs in Malawi using an LS model. The units being analyzed comprise of the TEs’ written lesson plans and qualitative content analysis is the chosen analytical approach. Findings Based on the analyzed research lesson plans, the TEs have difficulty in focusing on their own learning parallel to the student teachers’ (STs’) learning, and struggle with predicting STs’ responses to tasks. In addition, there is a pervasive lack of emphasis on planned and focused observation of STs’ learning, as evidenced by a review of the research lesson plans. Research limitations/implications This is a small-scale study due to LS being introduced to Malawi teacher education for the first time and the need to test before possible upscaling. Practical implications The paper includes a description of mathematics TEs’ understanding of LS in an African context, which can be a valuable information for TEs who are attempting to use LS. Originality/value This paper fulfills an identified need to learn more about TEs’ understanding of LS worldwide.
Keywords: _C:Malawi MWI

Moving teachers to Malawi’s remote communities: A data-driven approach to teacher deployment - Asim, Salman; Chimombo, Joseph; Chugunov, Dmitry; Gera, Ravinder (International Journal of Educational Development, 2019)
Keywords: _C:Malawi MWI

Access and Use of Mobile Devices as Learning Tools: The Case of Domasi Teacher Training College in Malawi - Chimpololo, Andrew (2019)
Keywords: _C:Malawi MWI

An analysis of heutagogical practices through mobile device usage in a teacher training programme in Malawi - Chimpololo, Andrew (2019)
Keywords: _C:Malawi MWI; ⛔ No DOI found

Exploring Teachers' Special and Inclusive Education Professional Development Needs in Malawi, Namibia, and Zimbabwe. - Chitiyo, Morgan; Hughes, Elizabeth M.; Chitiyo, George; Changara, Darlington M.; Itimu-Phiri, Ambumulire; Haihambo, Cynthy; Taukeni, Simon G.; Dzenga, Chaidamoyo G. (International Journal of Whole Schooling, 2019)
Keywords: _C:Malawi MWI; ⛔ No DOI found

Human Resource Management - Hopkins, Liam (College publishing house, 2019)

Who benefits from abolishing secondary school fees in Malawi & what are the costs? - Kadzamira, Esme (Transforming Malawi: An Engagement on Affordable Secondary Education, Ministry of Education/ UNICEF, 2019)
Keywords: _C:Malawi MWI

Will the poorest children benefit from abolishing secondary school fees in Malawi” - Kadzamira, Esme (2019)
Keywords: _C:Malawi MWI; ⛔ No DOI found

The effects of community-based distribution of family planning services on contraceptive use: The case of a national scale-up in Malawi - Masiano, Steven P.; Green, Tiffany L.; Dahman, Bassam; Kimmel, April D. (Social Science & Medicine, 2019)
Keywords: _C:Malawi MWI

Using the decomposed theory of planned behaviour to understand university students’ adoption of WhatsApp in learning - Nyasulu, Chimango; Dominic Chawinga, Winner (E-Learning and Digital Media, 2019)

Lusting, learning and lasting in school: sexual debut, school performance and dropout among adolescents in primary schools in Karonga district, northern Malawi - Sunny, Bindu S.; DeStavola, Bianca; Dube, Albert; Price, Alison; Kaonga, Allan M.; Kondowe, Scotch; Crampin, Amelia C.; Glynn, Judith R. (Journal of Biosocial Science, 2019)
Abstract Age at sexual debut is known to have implications for future sexual behaviours and health outcomes, including HIV infection, early pregnancy and maternal mortality, but may also influence educational outcomes. Longitudinal data on schooling and sexual behaviour from a demographic surveillance site in Karonga district, northern Malawi, were analysed for 3153 respondents between the ages of 12 and 25 years to examine the association between sexual debut and primary school dropout, and the role of prior school performance. Time to dropout was modelled using the Fine and Gray survival model to account for the competing event of primary school completion. To deal with the time-varying nature of age at sexual debut and school performance, models were fitted using landmark analyses. Sexual debut was found to be associated with a five-fold increase in rate of subsequent dropout for girls and a two-fold increase in dropout rate for boys (adjusted hazard ratio [aHR] of 5.27, CI 4.22–6.57, and 2.19, CI 1.77–2.7, respectively). For girls who were sexually active by age 16, only 16% ultimately completed primary schooling, compared with 70% aged 18 or older at sexual debut. Prior to sexual debut, girls had primary completion levels similar to those of boys. The association between sexual debut and school dropout could not be explained by prior poor school performance: the effect of sexual debut on dropout was as strong among those who were not behind in school as among those who were overage for their school grade. Girls who were sexually active were more likely to repeat a grade, with no effect being seen for boys. Pathways to dropout are complex and may differ for boys and girls. Interventions are needed to improve school progression so children complete primary school before sexual debut, and to improve sex education and contraception provision.
Keywords: _C:Malawi MWI

Teacher Professional Development around the World: The Gap between Evidence and Practice - Popova, Anna; Evans, David K.; Breeding, Mary E.; Arancibia, Violeta (World Bank, 2018)
Keywords: C:Low- and middle-income countries; STC-TLC; __C:filed:1; _genre:LR-literature_review

Mobile Instant Messaging (MIM) to support teaching practice: Insights from a nurse tutor program in Nigeria - Ajuwon, Ademola (Malawi Medical Journal, 2018)
AimTo determine the feasibility of using the Mobile Instant Messaging (MIM) platform, WhatsApp, to provide supervision and support for student nurse tutors during a teaching practice placement in Nigeria. Methods A descriptive qualitative method was used to design and evaluate a six-week WhatsApp group discussion intervention among 19 student nurse tutors. Two pre-intervention focus group sessions (n=9 and n=10) and a workshop were conducted to assess the students’ content needs and media usage, and to develop a short online supervisory curriculum. To evaluate the intervention, two focus group sessions (n=9 and n=9) were carried out, transcribed verbatim, and analysed together with the actual WhatsApp conversations using thematic content analysis.Findings The participants found the WhatsApp-enabled learning space valuable, in particular for the transfer and application of knowledge in their day-to-day teaching practice and, more generally, for their professional development. There were rich and multifaceted indicators of learning and professional development in evidence which were mostly triggered by specific facilitation techniques. The four themes from the WhatsApp conversations are: (1) sharing and discussing “tricks of the trade”; (2) providing direction and triggering reflective (teaching) practice; (3) sparking professional discussions and announcing professional development opportunities; and (4) maintaining a continuous moderating and teaching “presence”. ConclusionDespite some technical challenges centred mainly on the accessibility of the MIM space, the study identified indicators of good supervision practice and the results point to the feasibility and value of MIM to enhance supervision during teaching practice.
Keywords: Messaging; Mobile; Whatsup; _C:Malawi MWI

Dictionary of Mathematics in Sepedi Grade R-3 - Funda Wande (Funda Wande, 2018)
Keywords: _C:South Africa ZAF

Sustaining and Scaling Pedagogic Innovation in Sub-Saharan Africa: Grounded Insights For Teacher Professional Development - Haßler, Björn; Hennessy, Sara; Hofmann, Riikka (Journal of Learning for Development, 2018)
Developing sustainable and scalable educational initiatives is a key challenge in low-income countries where donor-funded short-term projects are limited by both contextual factors and programme design. In this commentary we examine some of the issues related to in-service teacher development in the context of sub-Saharan Africa, grounded predominantly in our work of over five years of iteratively developing, refining and evaluating an intensive school-based professional learning programme for primary school teachers. ‘OER4Schools’ integrates interactive pedagogy, Open Educational Resources (OER) and the use of mobile devices (where available). Our focus here is on identifying what the main factors are perceived to be in sustaining and scaling up such a programme, from the perspectives of participating teachers, workshop facilitators and the research team. Synthesising our previous research and drawing on recent work in the field, we identify the key characteristics of effective and sustainable professional learning in low-resourced contexts. Such characteristics include effective peer facilitation, school-based active learning, explicit programme structure, appropriate scheduling and resourcing, and mitigating resource constraints through the use of OER. Our conclusions offer insights concerning the importance and impact of wider influences on participation and engagement of stakeholders and lead to recommendations for future programme design and implementation.
Keywords: AWP2; Active Learning; Africa; Author:Haßler; Björn-CV-OECS; CitedIn:DFID_SRF; CitedIn:OER4S-TPE-Anon; CitedIn:OER4Schools-2012-HHH1-anon; CitedIn:PhD_Thesis; DIAL-RDO; Developing Nations; Educational Technology; Elementary Secondary Education; Faculty Development; Foreign Countries; Handheld Devices; IMPORT_FROM_DFID_RITE; InPrep; Inservice Teacher Education; Low Income Groups; Monday; Motivation; OER4Schools; Open Educational Resources; Peer Teaching; RPF-May-2016; Resource Allocation; Rural Schools; STC-TLC; Scaffolding (Teaching Technique); Scheduling; Shared Resources and Services; Sustainable Development; Sustainable Development Goal 4; TL:Arabic; TL:English; TL:Translated; Teacher Professional Development; Technology Uses in Education; Telecommunications; TranslationGoingAhead; _C:Bangladesh BGD; _C:Brazil BRA; _C:Cambodia KHM; _C:Cameroon CMR; _C:China CHN; _C:Ethiopia ETH; _C:Ghana GHA; _C:India IND; _C:Japan JPN; _C:Kenya KEN; _C:Nigeria NGA; _C:Rwanda RWA; _C:Sierra Leone SLE; _C:Singapore SGP; _C:South Africa ZAF; _C:Tanzania TZA; _C:Uganda UGA; _C:United Kingdom GBR; _C:United States USA; _C:Zambia ZMB; _C:Zimbabwe ZWE; __C:filed:1; __C:scheme:1; _bjoern_cv; _yl:a; missingHU; peer-facilitation; school-based active learning; sub-Saharan Africa

Gender and Education in Africa, 20 years on, Experiences from Malawi - Kadzamira, Esme (University of Cambridge, 2018)
Keywords: _C:Malawi MWI; ⛔ No DOI found

Who benefits from abolishing secondary school fees in Malawi, and what are the costs - Kadzamira, Esme; Rose, Pauline; Zubairi, Asma (World Education Blog. Global Education Monitoring Report.[online]. Available from: https://gemreportunesco. wordpress. com/2018/10/19/who-benefits-from-abolishing-secondary-school-fees-in-malawi-and-what-are-the-costs//>.[Accessed on 12th November 2018], 2018)
Keywords: _C:Malawi MWI; ⛔ No DOI found

National context and teacher characteristics: Exploring the critical non-cognitive attributes of novice teachers in four countries - Klassen, Robert M.; Durksen, Tracy L.; Al Hashmi, Waleed; Kim, Lisa E.; Longden, Ken; Metsäpelto, Riitta-Leena; Poikkeus, Anna-Maija; Györi, János G. (Teaching and Teacher Education, 2018)

Relating autonomy and capacity to higher education governance in Malawi: a case study on the University of Malawi, College of Medicine Reforms - Lino, Siphiwe Susan (2018)
Keywords: _C:Malawi MWI

‘I have learnt to love the child and give opportunities to play with peers’: A feasibility study of the training programme to support parents of young children with visual impairment in Malawi - Lynch, Paul; Gladstone, Melissa; McLinden, Michael; Douglas, Graeme; Jolley, Emma; Schmidt, Elena; Chimoyo, Josephine (Journal of Early Childhood Research, 2018)
This is a first mixed-methods study, which created, adapted and tested the feasibility of a training programme targeted at parents, community professionals, specialist teachers and volunteers to provide advice on developmental stimulation for children with visual impairment in their homes in rural and urban settings of Malawi. The study followed guidance from the Medical Research Council Framework for Developing and Evaluating Complex Interventions and drew on a bioecological model to help understand the feasibility of a new intervention in Malawi for 30 children with visual impairment and their carers in three districts of Southern Malawi. We trained 14 community workers and specialist teachers, then piloted the programme, which we linked to Care for Child Development (a World Health Organization/United Nations Children’s training package), over 6 months. In total, 10 observations were carried out to measure fidelity of the intervention at the child’s home. Acceptability was accessed through 20 post-intervention interviews and a focus group discussion with carers. Findings show that the new programme enabled workers and parents to be more positive towards their children with disabilities, improving relationships and responsiveness in their interactions. Drawing on the findings of the feasibility study, outcomes identified for a trial include measures of communication, child development, family care environment, participation and inclusion. This study has significance in providing a methodology that can be drawn upon to develop similar training programmes for use with children with a wider range of disabilities. The article has particular relevance to institutions and organisations working in early childhood development in that it provides a model to aid the development of tailored training programmes for children with visual impairment. It puts forward a table of 10 key messages on how best to prepare young children with visual impairment for life at school and for life after school.
Keywords: _C:Malawi MWI

Does the University-Industry Link Affect Solving Challenges of the Job Market? Lessons From Teacher Education and the Ministry of Education in Malawi - Mkandawire, Matthews Tiwaone; Luo, Zubing; Maulidi, Felix Kondwani (Journal of Medical Education and Curricular Development, 2018)
Keywords: _C:Malawi MWI

Who should be deciding what to be taught in schools? Perspectives from secondary school teacher education in Malawi - Mkandawire, Matthews Tiwaone; Maulidi, Felix Kondwani; Sitima, James; Luo, Zubing (Journal of medical education and curricular development, 2018)
Keywords: _C:Malawi MWI

Annual Report - Roger Federer Foundation (Roger Federer Foundation -, 2018)

Why do postgraduate students commit plagiarism? An empirical study - Selemani, Apatsa; Chawinga, Winner Dominic; Dube, Gift (International Journal for Educational Integrity, 2018)

Mapping an open digital university in Malawi: Implications for Africa - Zozie, Paxton; Chawinga, Winner Dominic (Research in Comparative and International Education, 2018)
The ubiquity of information and communication technologies (ICTs) have considerably transformed the higher educational landscape and are now providing an increasing number of novel and dynamic pathways for education delivery. The steady growth of flexible and affordable ICTs is impacting upon the higher education domain resulting in a departure from traditional education systems to more technologically driven forms of pedagogy. The purpose of this study was to investigate how best to exploit the available ICT infrastructures to support the creation of an open digital university at Mzuzu University in Malawi and to investigate the implications on a wider African context. The data were collected from lecturers, campus-based undergraduate students, and open and distance learning undergraduate students. The main results reveal that students and lecturers at Mzuzu University are conversant with a plethora of ICTs that can be adopted and customised to create a digital university. In that regard, we conclude that a digital university is possible in Malawi. We further conclude that, considering that African universities operate in mostly similar economic, technological and political landscapes, African universities are ready to embrace the concept of a digital university. This is regardless of the prevailing challenges.
Keywords: _C:Malawi MWI

A Survey of ICT Capacity in Ghana's Public Colleges of Education (Transforming Teacher Education and Learning, 2017)
The survey of ICT capacity at 40 colleges of education (CoEs) reflects a considerable amount of work, by many people. The National Council for Tertiary Education (NCTE) acknowledges with thanks, Consumer Insights Consult (CiC) research team, Cyprian Ekor, Elvis Akpabli, Emmanuel Mireku, George Asare, Kennedy Amedume, Daniel Amewuda, Philemon Opoku. NCTE staff, Jacob T. Akunor, Anthony Dzidzornu, Emmanuel Attey Yebuah, Ebenezer Osei Adu, Nicholas Ameyaw and Kwaku Gyampoh. Transforming Teaching and Learning in Ghana (T-TEL) staff, Dr. Björn Haßler, Dr. Rosie Lugg, Mr. Charlie Gordon, Ms. Beryl Opong-Agyei, Dr. Rich Tobin and Ms. Caroline Jordan. Particular thanks is extended to Jacob Tetteh Akunor, who led this exercise on behalf of the NCTE and to the Senior managers, ICT tutors, ICT technicians and student teacher participants at all 40 CoE that participated, and gave so generously of their time and expertise.
Keywords: Author:Haßler; _C:Ghana GHA; _zenodoODE; docs.opendeved.net

Education for democratic citizenship in Malawian secondary schools: balancing student voice and adult privilege - Namphande, Peter; Clarke, Linda; Farren, Sean; McCully, Alan (Compare: A Journal of Comparative and International Education, 2017)
Keywords: _C:Malawi MWI

Fighting resource scarcity – sustainability in the education system of Malawi – case study of Karonga, Mzimba and Nkhata Bay district - Kretzer, M. M.; Engler, S.; Gondwe, J.; Trost, E. (South African Geographical Journal, 2017)
Keywords: _C:Malawi MWI

Prevalence of mobile phone use in academic and social life of students and educators - Ndiku Makewa, Lazarus; Magaleta, Isaac; Role, Jesse (Journal of Scientific Research and Studies, 2017)
The researcher administered the questionnaires to 30 respondents who comprised four groupings namely, 8 teachers, 20 form four students, 1 head teacher and 1 district education officer. The group was considered representative of the target population. This study investigated the prevalence of mobile phone use in academic and social life of students and educators in government boarding schools of Shire Highlands Education Division, Southern Malawi. Both descriptive and comparative research designs were used. Four hundred and forty four (444) respondents participated. Questionnaires were used as instruments for data collection. A pilot study was done with 30 respondents participating. The respondents comprised four groupings namely, 8 teachers, 20 form four students, 1 head teacher and 1 district education officer. The group was considered representative of the target population. Reliability was established by computing Cronbach’s Alpha Coefficient. The alpha coefficients of 0.65 (Academic Life) and 0.60 (Social Life) were yielded. The study indicates that students often communicate with their parents about their academic performance. This suggests that students find it easy to communicate with their parents about their academic performance over the mobile phone because the parents give them such freedom whereas at school such opportunity is limited. Likewise, students often use mobile phones to record and save information and find notes and meaning of words. Teachers use mobile phones in accessing educational materials and finding notes for teaching. The head teachers use phones to access administrative reports, information dealing with school management, recording, saving and retrieving information and communicating with parents on school issue. On social life, the respondents use phones in keeping touch with parents and Heads of Departments. This study suggests that parents and schools encourage students to use their phones in a responsible manner, especially on academic matters.
Keywords: _C:Malawi MWI; ⛔ No DOI found

Dialogical theatre: reconsidering the role of Theatre for Development for malaria prevention in Malawi - Chisiza, Z. D. (Bloomsbury Methuen Drama, 2017)
This research snapshot examines the practice of Theatre for Development (TfD) in Malawi. It argues that, recently, Malawian TfD has been restricted to a tool for advancing the agendas and the goals of local NGOs funders rather than a real process of community transformation. It suggests that Paulo Freire’s problem-posing, or dialogical pedagogy — a method of learning where teacher and learner, as equals, engage in a collaborative process of problem exploration and solution finding — has been lost. The fact that practitioners in Malawi do not know of Freirian principles and have become so reliant on NGO communication briefs, results in work that is patronising and simplistic. I illustrate my argument with a look at one particular NGO use of message-based TfD.
Keywords: _C:Malawi MWI

Taking social media to a university classroom: teaching and learning using Twitter and blogs - Chawinga, Winner Dominic (International Journal of Educational Technology in Higher Education, 2017)

Achieving schooling for all in Africa: Costs, commitment and gender - Colclough, Christopher; Al-Samarrai, Samer; Rose, Pauline; Tembon, Mercy (Routledge, 2017)

‘Maybe I will give some help…. maybe not to help the eyes but different help’: an analysis of care and support of children with visual impairment in community settings in Malawi: Supporting young children with visual impairment in Malawi - Gladstone, M.; McLinden, M.; Douglas, G.; Jolley, E.; Schmidt, E.; Chimoyo, J.; Magombo, H.; Lynch, P. (Child: Care, Health and Development, 2017)
Keywords: _C:Malawi MWI

INVESTIGATING THE ROLE OF HISTORY OF MATHEMATICAL CONCEPTS IN LEARNING MATHEMATICS IN UPPER SECONDARY SCHOOL LEVEL IN MALAWI - KATHUMBA, COSMAS (2017)
Keywords: _C:Malawi MWI

Short-term impacts of an unconditional cash transfer program on child schooling: Experimental evidence from Malawi - Kilburn, Kelly; Handa, Sudhanshu; Angeles, Gustavo; Mvula, Peter; Tsoka, Maxton (Economics of Education Review, 2017)
Keywords: _C:Malawi MWI

Analysis of factors affecting pupil performance in Malawi’s primary schools based on SACMEQ survey results - Mulera, David Mc W.J.; Ndala, Ken Kaziputa; Nyirongo, Richard (International Journal of Educational Development, 2017)
Keywords: _C:Malawi MWI

An exploration of mathematical knowledge for teaching geometric proofs - Mwadzaangati, LISNET ELIZABETH NAMPINGA (Unpublished doctoral dissertation, University of Malawi, Zomba, Malawi. Retrieved from http://repository. cc. ac. mw, 2017)
Keywords: _C:Malawi MWI; ⛔ No DOI found

Developing a Culture of Readers: Complementary Materials That Engage - Sailors, Misty; Kaambankadzanja, Davie (The Reading Teacher, 2017)

An Assessment of Girls’ Dropout in in Dar es Salaam Secondary Schools: Perceptions and Experiences of Stakeholders - Shaweji, Titty Nasser (The Open University of Tanzania, 2017)

Failing to progress or progressing to fail? Age-for-grade heterogeneity and grade repetition in primary schools in Karonga district, northern Malawi - Sunny, Bindu S.; Elze, Markus; Chihana, Menard; Gondwe, Levie; Crampin, Amelia C.; Munkhondya, Masoyaona; Kondowe, Scotch; Glynn, Judith R. (International Journal of Educational Development, 2017)
Keywords: _C:Malawi MWI

Developing a strategy to address low youth education attendance in Malawi - Usi, Michael B. (2017)
Keywords: _C:Malawi MWI; ⛔ No DOI found

Open Educational Resources Guide for Colleges of Education - Haßler, Björn (T-TEL Professional Development Programme, 2016)
Keywords: Author:Haßler; _C:Ghana GHA

Theme 6: Leadership for Learning (Coordinators) - Swaffield, Sue; MacBeath, J. (T-TEL Professional Development Programme (Handbook for Professional Development Coordinators), 2016)
Keywords: Author:Haßler; _C:Ghana GHA

Theme 6: Leadership for Learning (Tutors) - Swaffield, Sue; MacBeath, J. (T-TEL Professional Development Programme (Professional Development Guide for Tutors), 2016)
Keywords: Author:Haßler; _C:Chad TCD; _C:Ghana GHA; _C:Greece GRC; _C:United Kingdom GBR; _C:Uruguay URY; __C:filed:1; __C:scheme:1

Theme 5: Teaching and learning materials (Coordinators) - Haßler, Björn (T-TEL Professional Development Programme (Handbook for Professional Development Coordinators), 2016)
Keywords: Author:Haßler; _C:Ghana GHA

Theme 5: Teaching and Learning Materials (Tutors) - Haßler, Björn (T-TEL Professional Development Programme (Professional Development Guide for Tutors), 2016)
Keywords: Author:Haßler; _C:Ghana GHA

Inference generation and text comprehension in bilingual children: A case study - Hara, Agness; Tappe, Heike (Literator, 2016)
The current study explores inference-making processes in 10–12-year-old bilingual Malawian children who either listened to stories in their primary language, or L1 (Chichewa), as compared to their secondary language (L2) (English), or viewed cartoon films containing no verbal content. The 127 children who participated in the study were divided into six groups characterised by different conditions of stimulus presentation – stimuli varied with respect to their modality (non-verbal film versus pre-recorded stories) or the language of stimulus presentation (English or Chichewa). The results indicate that the pre-recorded audio recordings seem to have supported inference-making more than the corresponding wordless films. This finding illustrates the significance of linguistically presented content. The linguistically presented content elicited even more inferences when it was presented in the children’s L1 (Chichewa) rather than in their medium of academic instruction (English). However, the results also indicate that the children from the private school (with English as a medium of instruction) drew more inferences than the children from the public school (where Chichewa is the medium of instruction). Furthermore, the results reveal that while the children were able to use knowledge transfer from a variety of knowledge bases to draw inferences, the inferencing process was impeded when the story content deviated too much from their own experiences. Lastly we found indications of variations in inferencing patterns that seemed to correlate to the language in which the stimulus material was presented and responded to.

Mathematics education and language diversity: The 21st ICMI Study - Barwell, Richard; Clarkson, Philip; Halai, Anjum; Kazima, Mercy; Moschkovich, Judit; Planas, Núria; Phakeng, Mamokgethi; Valero, Paola; Ubillús, Martha (2016)
This book examines multiple facets of language diversity and mathematics education. It features renowned authors from around the world and explores the learning and teaching of mathematics in contexts that include multilingual classrooms, indigenous education, teacher education, blind and deaf learners, new media and tertiary education. Each chapter draws on research from two or more countries to illustrate important research findings, theoretical developments and practical strategies. © The Editor(s) and the Author(s) 2015, corrected publication 2021 Open Access This book was originally published with exclusive rights reserved by the Publisher in 2015 and was licensed as an open access publication in March 2021 under the terms of the Creative Commons Attribution-NonCommercial-NoDerivatives 4.0 International License (http://creativecommons.org/licenses/ by-nc-nd/4.0/), which permits any noncommercial use, sharing, distribution and reproduction in any medium or format, as long as you give appropriate credit to the original author(s) and the source, provide a link to the Creative Commons licence and indicate if you modified the licensed material. You do not have permission under this licence to share adapted material derived from this book or parts of it. The book homepage is: https://link.springer.com/book/10.1007%2F978-3-319-14511-2#about
Keywords: _C:Malawi MWI

Policy & Practice A Development Education Review - Oonyu, Joseph; Kazima, Mercy; Tembe, Cristina; Clarke, Linda; Abbott, Lesley (2016)
There is a global recognition of the importance of the quality of teachers for the quality of education in schools and, whilst there is less unanimity about exactly how and where student teachers should be educated, there is consensus around the importance of the professional learning which takes place during the practicum or teaching practice. In this article, such learning is viewed through the lens of Lave and Wenger’s conception of ‘legitimate peripheral participation’ and, using questionnaires, through the eyes of student teachers in Malawi, Mozambique, Northern Ireland and Uganda. The issues raised by the students presented both distinctive commonalities, particularly around mentoring, and also localised issues, such as rudimentary resource provision. Everything depended, however, on the establishment of intentionally structured support mechanisms which recognise the value and distinctive nature of these important periods of initial professional learning.
Keywords: _C:Malawi MWI

Use of Mathematical Tasks of Teaching and the Corresponding LMT Meaures in the Malawi Context - Kazima, Mercy; Jakobsen, Arne; Nkhoma Kasoka, Dun (The Mathematics Enthusiast, 2016)
We discuss the adaptation and piloting of the previously developed U.S.-specific measures of mathematical knowledge for teaching to the Malawi context. The purpose is to produce measures that can be used to evaluate changes in mathematical knowledge for teaching gained through primary teacher education, thus informing teacher educators on the most effective evidence-based practices. By interviewing 14 teachers, we first examine whether the 16 recurrent mathematical tasks of teaching tasks identified in the U.S. are applicable to the Malawi context. This is followed by the discussion of the adaptability of the U.S. developed number concept and operations LMT measures. Next, we report on the item psychometric properties estimated from a pilot study in which 351 preservice primary school teachers participated at the end of their coursework. Our findings suggest that all the 16 tasks of teaching mathematics are applicable to the Malawi context, albeit to varying degrees, and should be complemented by additional tasks suggested by the Malawi teachers. For the LMT measures, we found that the majority of the LMT items psychometrically function well in the Malawi context and that item difficulty estimated in Malawi was strongly correlated with that reported in the U.S. We thus argue that there is some generality to the mathematics teaching tasks across the two contexts, as well as some specificity to Malawi, and that the adapted LMT measures can be used in a Malawi context. © 2016 The Author(s) & Dept. of Mathematical Sciences-The University of Montana.
Keywords: _C:Malawi MWI

Theme 4: Group Work (Coordinators) - Haßler, Björn (T-TEL Professional Development Programme (Handbook for Professional Development Coordinators), 2016)
Keywords: Author:Haßler; _C:Ghana GHA

Theme 4: Group Work (Tutors) - Haßler, Björn (T-TEL Professional Development Programme (Professional Development Guide for Tutors), 2016)
Keywords: Author:Haßler; _C:Ghana GHA

Theme 3: Talk for Learning (Coordinators) - Haßler, Björn (T-TEL Professional Development Programme (Handbook for Professional Development Coordinators), 2016)
Keywords: Author:Haßler; _C:Ghana GHA

Theme 3: Talk for Learning (Tutors) - Haßler, Björn (T-TEL Professional Development Programme (Professional Development Guide for Tutors), 2016)
Keywords: Author:Haßler; _C:Ghana GHA

Introduction: An ICMI Study on Language Diversity in Mathematics Education - Barwell, Richard; Clarkson, Philip; Halai, Anjum; Kazima, Mercy; Moschkovich, Judit; Planas, Núria; Phakeng, Mamokgethi; Valero, Paola; Ubillús, Martha (2016)
This chapter provides the introduction to this ICMI Study 21 volume. It includes: a discussion of the place of this study and its topic within ICME; a discussion of what is meant by the study title; and a brief historical account of research on this topic in mathematics education. The chapter also recounts the various stages of the study, including the development of the discussion document, the study conference, and the preparation of this volume. The latter parts of the chapter include syntheses of some key research ideas emerging from the volume, implications for policy and practice and issues for further research. © The Editor(s) and the Author(s) 2015, corrected publication 2021 Open Access This book was originally published with exclusive rights reserved by the Publisher in 2015 and was licensed as an open access publication in March 2021 under the terms of the Creative Commons Attribution-NonCommercial-NoDerivatives 4.0 International License (http://creativecommons.org/licenses/ by-nc-nd/4.0/), which permits any noncommercial use, sharing, distribution and reproduction in any medium or format, as long as you give appropriate credit to the original author(s) and the source, provide a link to the Creative Commons licence and indicate if you modified the licensed material. You do not have permission under this licence to share adapted material derived from this book or parts of it. The book homepage is: https://link.springer.com/book/10.1007%2F978-3-319-14511-2#about
Keywords: _C:Malawi MWI

Challenges and Opportunities for Second Language Learners in Undergraduate Mathematics - Durand-Guerrier, Viviane; Kazima, Mercy; Libbrecht, Paul; Ngansop, Judith; Salekhova, Leila; Tuktamyshov, Nail; Winsløw, Carl (2016)
In this chapter, we describe challenges and opportunities that second language learners face in undergraduate mathematics programs. The presence of such students is nowadays common in many undergraduate courses due to migration, student mobility, and other factors. We provide examples of various multilingual contexts at the university level, summarize insights from international research on this topic, and present emergent proposals for helping students to overcome these challenges. This chapter highlights the importance of continuing research on the topic of second language learners in undergraduate mathematics courses so that we can offer research-based approaches to improve undergraduate mathematics teaching in multilingual contexts. This chapter will support the mathematics education research community involved in advanced mathematics, as well as instructors and policy makers, to develop awareness of the issues involved in undergraduate mathematics learning and teaching for second language learners.
Keywords: _C:Malawi MWI

T-TEL school partnership innovation (2016)
Keywords: _C:Ghana GHA

A case study of instructional leadership in Malawian secondary schools - BEYTEKİN, Osman Ferda; TOPRAKÇI, Erdal; CHIPALA, Hussein Collins (İnönü Üniversitesi Eğitim Fakültesi Dergisi, 2016)
Keywords: _C:Malawi MWI; ⛔ No DOI found

Teaching and learning 24/7 using Twitter in a university classroom: Experiences from a developing country - Chawinga, Winner Dominic (E-Learning and Digital Media, 2016)
It is understood that microblogging (tweeting) which is a form of Web 2.0, has been a centre of attraction in some institutions of higher education. However, despite its hype and pomp as reported by some scholars in developed countries, integration of Twitter in a classroom environment in developing countries is just beginning to flourish. In Malawi for example, it remains unknown how Twitter can be effectively assimilated into a university classroom to enhance teaching and learning. In this study therefore, I report on the findings about the practical use of Twitter in two university courses offered in the Department of Library and Information Science at Mzuzu University in Malawi. Findings of the study show that if properly deployed, Twitter is indeed an impetus of the much hailed learner-centred approach to teaching and learning. With the use of Twitter, I found that students shared and discussed course content with colleagues and me (lecturer) 24/7. Specifically, with the proliferation of Internet enabled phones and other mobile devices in Malawi, the study found that it was possible for students to generate out-of-class discussions and learn from each other without necessarily meeting physically. In addition, students were key contributors to their own learning as it was possible to effectively search, generate and share their own content through creating knowledge collaboratively. However, limited access to the Internet (due to unavailability of Wi-Fi) by students coupled with exorbitant Internet bundles, remain key challenges against the effective appropriation of Twitter in a university classroom.

Increasing access to higher education through open and distance learning: Empirical findings from Mzuzu University, Malawi - Chawinga, Winner Dominic; Zozie, Paxton Andrew (International Review of Research in Open and Distributed Learning, 2016)
Keywords: _C:Malawi MWI

What Really Works to Improve Learning in Developing Countries? An Analysis of Divergent Findings in Systematic Reviews [World Bank Research Observer] - Evans, David K.; Popova, Anna (The World Bank Research Observer, 2016)
Keywords: C:Low- and middle-income countries; STC-TLC; __C:filed:1; ___duplicate_item; _genre:LR-literature_review

Theme 1: Creative Approaches (Student Teachers) - Haßler, Björn (T-TEL Professional Development Programme (Professional Develoment Guide for Student Teachers), 2016)
Keywords: Author:Haßler; _C:Ghana GHA

Theme 2: Questioning (Student Teachers) - Haßler, Björn (T-TEL Professional Development Programme (Professional Develoment Guide for Student Teachers), 2016)
Keywords: Author:Haßler; _C:Ghana GHA

Theme 3: Talk for Learning (Facilitators) - Haßler, Björn (T-TEL Professional Development Programme (Handbook for Facilitators), 2016)
Keywords: Author:Haßler; _C:Ghana GHA

Theme 3: Talk for Learning (Student Teachers) - Haßler, Björn (T-TEL Professional Development Programme (Professional Develoment Guide for Student Teachers), 2016)
Keywords: Author:Haßler; _C:Ghana GHA

Theme 4: Group Work (Facilitators) - Haßler, Björn (T-TEL Professional Development Programme (Handbook for Facilitators), 2016)
Keywords: Author:Haßler; _C:Ghana GHA

Theme 4: Group Work (Student Teachers) - Haßler, Björn (T-TEL Professional Development Programme (Professional Develoment Guide for Student Teachers), 2016)
Keywords: Author:Haßler; _C:Ghana GHA

Theme 5: Teaching and Learning Materials (Facilitators) - Haßler, Björn (T-TEL Professional Development Programme (Handbook for Facilitators), 2016)
Keywords: Author:Haßler; _C:Ghana GHA

Theme 5: Teaching and Learning Materials (Student Teachers) - Haßler, Björn (T-TEL Professional Development Programme (Professional Develoment Guide for Student Teachers), 2016)
Keywords: Author:Haßler; _C:Ghana GHA

Theme 6: Leadership for Learning Materials (Facilitators) - Haßler, Björn (T-TEL Professional Development Programme (Handbook for Facilitators), 2016)
Keywords: Author:Haßler; _C:Ghana GHA

Theme 6: Leadership for Learning (Student Teachers) - Haßler, Björn (T-TEL Professional Development Programme (Professional Develoment Guide for Student Teachers), 2016)
Keywords: Author:Haßler; _C:Ghana GHA

A global north-south evaluation of partnership support for student teachers on placement - Kazima, Mercy; Tembe, Cristina; Oonyu, Joseph; Clarke, Linda; Abbott, Lesley (A Development Education Review, 2016)
Keywords: _C:Malawi MWI; ⛔ No DOI found

Improving higher education in Malawi for competitiveness in the global economy - Mambo, Michael; Meky, Muna; Tanaka, Nobuyuki; Salmi, Jamil (World Bank Publications, 2016)
Keywords: _C:Malawi MWI

Exploring personality traits, mindfulness and sense of coherence of women working in higher education - Mayer, Claude-Hélène; Visser, Delene; Surtee, Sabie (SA Journal of Human Resource Management, 2016)
Keywords: ⛔ No DOI found

What Mismatch Challenges are there between What Teacher Education Institutions Teach and What is Expected at Work Place? Retrospective Views of Secondary School Teachers from Tanzania and Malawi Studying in China. - Mkandawire, Matthews Tiwaone; Mwanjejele, Janeth N.; Luo, Zubing; Ruzagiriza, Angel Umubyeyi (American Academic Scientific Research Journal for Engineering, Technology, and Sciences, 2016)
Keywords: _C:Malawi MWI; ⛔ No DOI found

Mobile Phones and Education in Sub-Saharan Africa: From Youth Practice to Public Policy: Mobile Phones and Education in Africa - Porter, Gina; Hampshire, Kate; Milner, James; Munthali, Alister; Robson, Elsbeth; de Lannoy, Ariane; Bango, Andisiwe; Gunguluza, Nwabisa; Mashiri, Mac; Tanle, Augustine; Abane, Albert (Journal of International Development, 2016)

Interactive Learning and Teaching (iACT): Zonal In-Service Coordinators Facilitation Guide - Roger Federer Founation (2016)

Theme 2: Questioning (Coordinators) - Haßler, Björn (T-TEL Professional Development Programme (Handbook for Professional Development Coordinators), 2015)
Keywords: Author:Haßler; _C:Ghana GHA

Theme 2: Questioning (Tutors) - Haßler, Björn (T-TEL Professional Development Programme (Professional Development Guide for Tutors), 2015)
Keywords: Author:Haßler; _C:Ghana GHA

The Effects of Educational Externalities on Maize Production in Rural Malawi - Mussa, Richard (Oxford Development Studies, 2015)
Keywords: _C:Malawi MWI

Theme 1: Creative Approaches (Coordinators) - Haßler, Björn (T-TEL Professional Development Programme (Handbook for Professional Development Coordinators), 2015)
Keywords: Author:Haßler; _C:Ghana GHA

Theme 1: Creative approaches (Tutors) - Haßler, Björn (T-TEL Professional Development Programme (Professional Development Guide for Tutors), 2015)
Keywords: Author:Haßler; _C:Ghana GHA

The Case of Chichewa and English in Malawi: The Impact of First Language Reading and Writing on Learning English as a Second Language - Shin, Jaran; Sailors, Misty; McClung, Nicola; Pearson, P. David; Hoffman, James V.; Chilimanjira, Margaret (Bilingual Research Journal, 2015)
Keywords: _C:Malawi MWI

Youth wage employment and parental education in Malawi - Mussa, Richard (Development Southern Africa, 2015)
Keywords: _C:Malawi MWI

Students’ Reasons for Preferences of Contexts in Learning Mathematics - Kazima, Mercy (Journal of Education and Training Studies, 2015)
This paper reports on findings from a study that investigated reasons Malawian students have for preferring particular contexts in mathematics. The study explored students’ preferences of contexts using a survey questionnaire that contained 27 contexts and asked students to indicate their level of interest for each context on a 4-point scale and to write down reasons for their most preferred contexts. There were 393 students of 14-20 years old. Findings include that most preferred contexts were of future career prospects, modern technology, health and community issues. Students’ reasons for these preferences were in four categories of career prospects, curiosity, community well-being and personal well-being. Furthermore, future career prospects was the most common reason for the preferred contexts.
Keywords: _C:Malawi MWI

Technology Education and Developing Countries - Banks, Frank; Chikasanda, Vanwyk K. M. (The Future of Technology Education, 2015)

Barriers and enablers to inclusion in education for children with disabilities in Malawi - Banks, L. M.; Zuurmond, M. (Norwegian Association of Disabled: Oslo, Norway, 2015)
Keywords: _C:Malawi MWI; ⛔ No DOI found

Introducing technology studies in Malawi’s model primary schools: towards building a technologically literate society - Chikasanda, Vanwyk Khobidi; Mgawi, Rabson Killion; Mtemang’ombe, Doris; Alide, Yusuf (International Journal of Technology and Design Education, 2015)
Keywords: _C:Malawi MWI

Mobile e-learning: The choice between Responsive/Mobile Websites and Mobile Applications for Virtual Learning Environments for increasing access to Higher Education in Malawi - Chilivumbo, Chifundo (2015 IST-Africa Conference, 2015)
Keywords: _C:Malawi MWI

Special education teacher preparation in Kenya, Malawi, Zambia, and Zimbabwe - Chitiyo, Morgan; Odongo, George; Itimu-Phiri, Ambumulire; Muwana, Florence; Lipemba, Mary (Journal of International Special Needs Education, 2015)
Keywords: _C:Malawi MWI

Developing Great Teaching: Lessons from the international reviews into effective professional development. - Cordingley, P; Huggins, S; Greany, T; Buckley, N; Coles-Jordan, D; Crisp, B; Saunders, L; Coe, R (Teacher Development Trust, 2015)
Developing Great Teaching: Lessons from the international reviews into effective professional development In September 2014 the Teacher Development Trust, with kind support from TES Global, commissioned a review of the international research into what constitutes effective professional development for teachers. The review was conducted by an...
Keywords: C:England / International; STC-TLC; __C:filed:1; ___working_potential_duplicate; ⛔ No DOI found

Context matters: fostering, orphanhood and schooling in sub-saharan africa - Hampshire, Kate; Porter, Gina; Agblorti, Samuel; Robson, Elsbeth; Munthali, Alister; Abane, Albert (Journal of Biosocial Science, 2015)
Summary A growing body of research suggests that orphanhood and fostering might be (independently) associated with educational disadvantage in sub-Saharan Africa. However, literature on the impacts of orphanhood and fostering on school enrolment, attendance and progress produces equivocal, and often conflicting, results. This paper reports on quantitative and qualitative data from sixteen field-sites in Ghana and Malawi, highlighting the importance of historical and social context in shaping schooling outcomes for fostered and orphaned children. In Malawi, which has been particularly badly affected by AIDS, orphans were less likely to be enrolled in and attending school than other children. By contrast, in Ghana, with its long tradition of ‘kinship fostering’, orphans were not significantly educationally disadvantaged; instead, non-orphaned, purposively fostered children had lower school enrolment and attendance than their peers. Understanding the context of orphanhood and fostering in relation to schooling is crucial in achieving ‘Education for All’.

Introduction to Professional Development (Coordinators) - Haßler, Björn (T-TEL Professional Development Programme (Handbook for Professional Development Coordinators), 2015)
Keywords: Author:Haßler; _C:Ghana GHA

Introduction to Professional Development (Facilitators) - Haßler, Björn (T-TEL Professional Development Programme (Handbook for Facilitators), 2015)
Keywords: Author:Haßler; _C:Ghana GHA

Introduction to Professional Development (Student Teachers) - Haßler, Björn (T-TEL Professional Development Programme (Professional Development Guide for Student Teachers)), 2015)
Keywords: Author:Haßler; _C:Ghana GHA

Introduction to Professional Development (Tutors) - Haßler, Björn (T-TEL Professional Development Programme (Professional Development Guide for Tutors), 2015)
Keywords: Author:Haßler; _C:Ghana GHA

The integration of ICTs into the learning activities of the college of medicine undergraduate students - Kalembera, Lloyd; Majawa, Felix (2015 IST-Africa Conference, 2015)

Teachers and the quality of basic education in sub-Saharan Africa - Lauwerier, Thibaut; Akkari, Abdeljalil (Education Research and Foresight: Working Papers Series, 2015)
Keywords: ⛔ No DOI found

Cloud computing adoption in Higher Education Institutions of Malawi: An exploratory study. - Makoza, Frank (International Journal of Computing & ICT Research, 2015)
Keywords: _C:Malawi MWI; ⛔ No DOI found

Graduate teachers’ perceptions and experiences about the usefulness of the secondary school teacher education project of Domasi College of Education in enabling teachers to improve their teaching competences, a master’s degree thesis submitted to University of Sussex - Moyo, J. (COLLEGE OF EDUCATION IN ENABLING TEACHERS TO IMPROVE THEIR TEACHING …, 2015)

Use of distance education for teacher training and development in Malawi: models, practices, and successes - Msiska, Fred Gennings Wanyavinkhumbo (2015)
Keywords: _C:Malawi MWI; ⛔ No DOI found

E-Education adoption in emerging economy countries: Case of Malawi - Mtingwi, Marian (2015 IST-Africa Conference, 2015)
Keywords: _C:Malawi MWI

Supporting teacher development: Literature review - Reid, Kate; Kleinhenz, Elizabeth (2015)
Keywords: ⛔ No DOI found

Tracing shadows: How gendered power relations shape the impacts of maternal death on living children in sub Saharan Africa - Yamin, Alicia Ely; Bazile, Junior; Knight, Lucia; Molla, Mitike; Maistrellis, Emily; Leaning, Jennifer (Social Science & Medicine, 2015)

Inside private secondary schools in Malawi: Access or exclusion? - Zeitlyn, Benjamin; Lewin, Keith M.; Chimombo, Joseph; Meke, Elizabeth (International Journal of Educational Development, 2015)
Keywords: _C:Malawi MWI

This is My Story: participatory performance for HIV and AIDS education at the University of Malawi - Jaganath, D.; Mulenga, C.; Hoffman, R. M.; Hamilton, J.; Boneh, G. (Health Education Research, 2014)
Keywords: _C:Malawi MWI

Prospects and constraints of staff development in the University of Malawi Libraries - Mapulanga, Patrick (The Bottom Line, 2014)
Purpose – The purpose of this paper is to look at staff development and its challenges in the University of Malawi Libraries. Design/methodology/approach – A case study design was used to collect qualitative and quantitative data. University Budget Estimates from 2004/2005 to 2010/2011 financial years were analysed. Data from the University of Malawi Strategic Plan 2005-2009 were examined. Interviews were conducted with college librarians in the University of Malawi Libraries. Documentary evidence was also used. Findings – Study findings indicate that staff development in the University of Malawi Libraries has emphasised on professional qualification in Library and Information Studies. However, due to financial constraints, the majority of the library staff lacks LIS professional qualifications. This study recommends that libraries should consider budgeting for continuing professional development (CPD). Practical implications – Staff development requires continuous funding and time. This study recommends the CPD approach to staff development in academic libraries. The study also recommends the introduction of an education levy to benefit skills and training needs for higher education institutions. Originality/value – There is dearth of literature on staff development in academic libraries in Malawi. This paper seeks to recommend CPD.
Keywords: _C:Malawi MWI

Primary school drop-outs breaking the vicious cycle - Cassie, BRIDGET C. (2014)
Keywords: _C:Malawi MWI

Implementing learner-centred approaches to instruction in primary schools in Malawi - Chiphiko, Emmanuel; Shawa, Lester Brian (Mediterranean Journal of Social Sciences, 2014)
Keywords: _C:Malawi MWI; ⛔ No DOI found

Is There an App for That? Connecting Local Knowledge with Scientific Literacy - Glasson, George E. (Assessing Schools for Generation R (Responsibility): A Guide for Legislation and School Policy in Science Education, 2014)
Mobile digital technologies, including laptops, tablet PCs, and smartphones, are used increasingly for communication, social networking, navigation, research, and documenting everyday life events. Thousands of application software (i.e., Apps) can be downloaded on electronic devices to assist in performing specific tasks such as cooking, birding, blazing a trail, sailing, recording music, and so forth. An important challenge for educators is to explore ways for enhancing classroom instruction, student learning, and achievement through these technologies. In the field of environmental education, there is a trend towards connecting local community knowledge with scientific literacy. Is there an App for that? This chapter explores environmental education projects that employ the use of emerging digital technologies and software applications to help students from diverse cultures connect local knowledge and practices with scientific literacy. After discussing the goal of achieving scientific literacy for all students in the K-12 schools, place-based education projects as part of the GLOBE Program and other projects in Africa and Thailand are discussed to demonstrate how digital technologies can be used to facilitate science learning, curriculum development, and authentic assessment.
Keywords: Authentic Assessment; Digital Technology; Globe Program; National Science Education Standard; Scientific Literacy

Evaluating the provision of flexible learning for children at risk of primary school dropout in Malawi - Jukes, Matthew C.H.; Jere, Catherine M.; Pridmore, Pat (International Journal of Educational Development, 2014)
Keywords: _C:Malawi MWI

Chronic Under-Completion in Malawi’s Primary Schools: Its trends and determinants - Kadzamira, Esme (2014)
Keywords: _C:Malawi MWI; ⛔ No DOI found

Universal basic education and the provision of quality mathematics in southern africa - Kazima, Mercy (International Journal of Science and Mathematics Education, 2014)
In this paper, I discuss Universal Basic Education (UBE) in relation to the teaching and learning of mathematics in Southern Africa. I present the status of UBE for all countries in the region and then use 3 selected examples: Botswana, Malawi, and Zambia, to illustrate the provision of mathematics in the general framework of UBE in the countries. I draw from results of SACMEQ evaluations to compare the 3 countries’ quality of primary education and also the mathematical achievement of learners. According to the evaluations, countries that have better age-appropriate enrolment and provide a better quality of primary education seem to have better mathematical achievement than countries that have less age-appropriate enrolment and less quality of primary education. While this might seem obvious, it is important to note because of the many challenges that some Southern African countries are facing in their efforts in providing quality mathematics education to all.
Keywords: _C:Malawi MWI

Identifying strategies to enhance the educational inclusion of visually impaired children with albinism in Malawi - Lynch, Paul; Lund, Patricia; Massah, Bonface (International Journal of Educational Development, 2014)
Keywords: _C:Malawi MWI

The “lifeworld” of Malawian undergraduate student nurses: The challenge of learning in resource poor clinical settings - Msiska, Gladys; Smith, Pam; Fawcett, Tonks (International Journal of Africa Nursing Sciences, 2014)
Background: In the ‘‘lifeworld’’ of student nurses, the clinical learning experience is indispensable. It plays a vital role in preparing them for their future nursing career. Aim: The aim of the study was to explore the students’ perceptions of their clinical learning experience, in view of the problems prevalent in the various clinical settings that are used as teaching hospitals. Design: This was a hermeneutic phenomenological study and the setting was a university nursing college in Malawi. The sample was selected purposively, consisting of thirty participants. Conversational interviews were conducted to obtain participants’ accounts of their clinical learning. A framework developed by modifying Colaizzi’s procedural steps guided the phenomenological analysis.
Keywords: _C:Malawi MWI

An investigation on challenges experienced by open day secondary schools running within a conventional secondary school: a case of katoto, rumphi and chilumba secondary schools. - Munyimbili, Joseph WC (Mzuzu University, 2014)

Household Expenditure Components and the Poverty and Inequality Relationship in Malawi: Household Expenditure Components - Mussa, Richard (African Development Review, 2014)
Keywords: _C:Malawi MWI

The Role of Bridge International Academy In Modernization: The Case of Kenya - Rees, Elizabeth Karen (United States International University-Africa, 2014)

Divisions of IAAP - Sinangil, Handan Kepir; Oakland, Thomas; Kağıtçıbaşı, Çiğdem; Hau, Kit-Tai; Blampied, Neville; Denmark, Florence; Luszczynska, Aleksandra; Kirchler, Erich; Allan, Alfred; Ito, Takehiko (Applied Psychology, 2014)
Keywords: ⛔ No DOI found

Students’ Preferences for Contexts and their Relevance to School Mathematics in Malawi - Kazima, Mercy (African Journal of Research in Mathematics, Science and Technology Education, 2013)
This paper looks at mathematics and its relevance in schools from the perspective of students' interests. It starts by discussing briefly the importance of paying attention to cultural and social relevance, and then it focuses on students' interests as one of the aspects of relevance. Findings are presented from a survey conducted in Malawi with 346 secondary school students. The study explored what students would find interesting to learn as contexts in school mathematics by indicating their preferences for some given contexts in form of a questionnaire, which was adapted from a very large cross country project (ROSME). Findings include that students are interested in mathematics for future careers and mathematics of modern technologies more than ethnomathematics and mathematics of agriculture, and there are no differences in preferences for contexts between female and male students. Most of the findings confirm findings from previous ROSME studies, particularly those situated in African countries, and therefore strengthen the arguments made earlier by these studies. This paper further argues that relevance for students includes their interests, and therefore should be considered as a factor in the development of curriculum materials and classroom activities.
Keywords: _C:Malawi MWI

Enhancing teachers’ technological pedagogical knowledge and practices: a professional development model for technology teachers in Malawi - Chikasanda, Vanwyk Khobidi Mbubzi; Otrel-Cass, Kathrin; Williams, John; Jones, Alister (International Journal of Technology and Design Education, 2013)
Keywords: _C:Malawi MWI

Teacher training and deployment in Malawi - DeStefano, Joseph (Teacher reforms around the world: Implementations and outcomes, 2013)
Keywords: _C:Malawi MWI

Inventory of University Of Malawi Studies Published In International Journals, 2005-2012 - Kakhongwe, Paul (2013)
Keywords: _C:Malawi MWI; ⛔ No DOI found

Malawi: Contemporary and critical issues - Kamwendo, Gregory (Education in Southern Africa, 2013)
Keywords: _C:Malawi MWI

Assessing final year undergraduate student teacher on school based teaching practice at the Polytechnic of the University Malawi: a dual assessment process - Kaphesi, Elias (African Journal of Teacher Education, 2013)
Keywords: _C:Malawi MWI

Prevalence and correlates of being bullied among in-school adolescents in Malawi: results from the 2009 Global School-Based Health Survey - Kubwalo, H. W.; Muula, Adamson S.; Siziya, Seter; Pasupulati, S.; Rudatsikira, Emmanuel (Malawi Medical Journal, 2013)
Keywords: _C:Malawi MWI; ⛔ No DOI found

Teacher motivation and implementation of continuing professional development programmes in Malawi - Meke, Elizabeth Selemani (The Anthropologist, 2013)
Keywords: _C:Malawi MWI

Rural–urban differences in parental spending on children's primary education in Malawi - Mussa, Richard (Development Southern Africa, 2013)
Keywords: _C:Malawi MWI

Dropping out of school as a threat for success for teenage girls in rural areas of Malawi: Motivating them for school completion - Sadyalunda, Rosemary (Eastern University, 2013)
Keywords: _C:Malawi MWI

‘Give courage to the ladies’: expansive apprenticeship for women in rural Malawi - Safford, Kimberly; Cooper, Deborah; Wolfenden, Freda; Chitsulo, Joyce (Journal of Vocational Education & Training, 2013)
Keywords: _C:Malawi MWI

At the Interface of Policy and Cultural Change - Samati, Madalo (Improving Learning Opportunities and Outcomes for Girls in Africa, 2013)
Keywords: _C:Malawi MWI; ⛔ No DOI found

Funding Higher Education in Sub-Saharan Africa - Teferra, Damtew (Palgrave Macmillan UK, 2013)

Theatre for a Change in Malawi: Participatory approaches to Development - HAHN, MATTHEW (Journal of Applied Arts & Health, 2012)
Theatre for a Change (TfaC) uses innovative strategies to empower vulnerable and marginalized groups through positive behaviour change and advocacy of gender and sexual equality. Adapting their practice from Augusto Boal's Forum Theatre, TfaC's aims to change attitudes towards gender and sexuality in specific communities within Malawi. When TfaC recognized that the Protagonist in their Forum Plays was predominantly female, re-enforcing the stereotype of women within these communities, they adapted Forum Theatre's concept of 'win/loss' to explore the issues of 'equality' where any character can be replaced in order to achieve an equality in the relationship represented on stage. They call this adaptation, Touch Tag Theatre. Touch Tag Theatre is currently used to positively change the behaviour of vulnerable and marginalized groups as well as to advocate for changes in educational and legislative policy decisions to those who hold power and influence in society on a wider level.
Keywords: African studies; Boalian theory and practice; Gender and sexual studies; Health care; Non-governmental organizations; Theatre for Development; _C:Malawi MWI

Managing national and international priorities: a framework for low-income countries: Managing national and international priorities - Burgis-Kasthala, Sarath; Kamiza, Steve; Bates, Imelda (Medical Education, 2012)

Adult mortality and probable cause of death in rural northern Malawi in the era of HIV treatment - Chihana, Menard; Floyd, Sian; Molesworth, Anna; Crampin, Amelia C.; Kayuni, Ndoliwe; Price, Alison; Zaba, Basia; Jahn, Andreas; Mvula, Hazzie; Dube, Albert; Ngwira, Bagrey; Glynn, Judith R.; et al. (Tropical Medicine & International Health, 2012)
Keywords: _C:Malawi MWI

Partnership for Education in Malawi: Power and Dynamics within the Education Sector Wide Approach - Chirwa, Catherine Sekanayo (University of Sussex, 2012)
Keywords: _C:Malawi MWI

Language-in-Education policies in conflict: Lessons from Malawian mathematics teacher training classrooms - Chitera, Nancy (African Journal of Research in Mathematics, Science and Technology Education, 2012)
Keywords: _C:Malawi MWI

School Participation And Pupil Performance: Baseline Survey - Chiuye, Grace; Selemani-Meke, Elizabeth; Kadzamira, Esme (2012)
Keywords: _C:Malawi MWI; ⛔ No DOI found

Alternative approaches to education provision for out-of-school youth in Malawi: The case of complementary basic education - Jere, Catherine M. (UNESCO, 2012)
Keywords: _C:Malawi MWI

Improving educational access of vulnerable children in high HIV prevalence communities of Malawi: The potential of open and flexible learning strategies - Jere, Catherine M. (International Journal of Educational Development, 2012)
Keywords: _C:Malawi MWI

Establishing and upgrading physical therapist education in developing countries: four case examples of service by Japan and United States physical therapist programs to Nigeria, Suriname, Mongolia, and Jordan - John, Emmanuel B.; Pfalzer, Lucinda A.; Fry, Donna; Glickman, Leslie; Masaaki, Sakamoto; Sabus, Carla; Okafor, Udoka AC; Al-Jarrah, Muhammed D. (Journal of Physical Therapy Education, 2012)

Cash Transfers and Children's Education and Labour among Malawi's Poor - Miller, Candace; Tsoka, Maxton (Development Policy Review, 2012)
Keywords: _C:Malawi MWI

University-School mentoring partnerships in teacher education: The case of the Maputo Municipality Schools - Moran, Anne; Tembe, Cristina CR; Cossa, Eugénia FR; Oonyu, Joseph; Otaala, Justine; Clarke, Linda; Kazima, Mercy; Kapito, Patrick MS; Farren, Sean N. (Revista Científica da UEM: Série Ciências da Educação, 2012)
Keywords: _C:Malawi MWI; ⛔ No DOI found

UNICEF Child Friendly Schooling (CFS) - Nampota, Dorothy; Jere, Catherine; Chiwaula, Lizzie; Meke, Elizabeth; Kadzamira, Esme (2012)
Keywords: _C:Malawi MWI; ⛔ No DOI found

Improving the Rural Investment Climate for Businesses - Sawada, Naotaka (2012)

Transition and Tertiary Education: A Case Study of Mzuzu University, Malawi - Zozie, Paxton Andrew; Kayira, Peter Benwell (Research in Comparative and International Education, 2012)
This article reviews the role of guidance and counselling in Malawi in reducing dropout and easing the transition of students to tertiary education, as well as in helping them during their time in tertiary education. It begins by identifying key success factors in guidance and counselling services for learners in both developed and developing countries. The article argues that the provision of viable secondary school careers guidance and changes to the university counselling programme could reduce the dropout rate and create a smoother transition for students during tertiary education with a positive impact on learning progression. The rationale for integrating guidance and counselling between school and tertiary provision is then explored. Drawing on case-study research carried out at Mzuzu University (MZUNI), the article presents findings on the preparation of students at secondary school for university education, the relationship of subjects offered at secondary school to courses pursued at university and the challenges faced by students as they start university and progress through the levels. The article concludes with some recommendations for enabling smoother transitions through the integration of school guidance and counselling in learning institutions.
Keywords: _C:Malawi MWI

Importance of Equating High-Stakes Educational Measurements - Chulu, Bob Wajizigha; Sireci, Stephen G. (International Journal of Testing, 2011)
Keywords: _C:Malawi MWI

Mathematical knowledge for teaching: Adding to the description through a study of probability in practice - Kazima, Mercy; Adler, Jill (Pythagoras, 2011)
In their description of the mathematical work of teaching, Ball, Bass & Hill (2004) describe the mathematical problem solving that teachers do as they go about their work. In this paper we add to this description through our study of teaching of probability in a grade 8 multilingual classroom in South Africa. We use instances of teaching to highlight the mathematical problem solving that teachers might face as they work with learners’ ideas, both expected and unexpected. We discuss the restructuring of tasks as an inevitable feature of teachers’ work, and argue that in addition to scaling up or scaling down of the task as Ball et al. (2004) describe, restructuring can also entail shifting the mathematical outcomes from those intended. We also point out how well known issues in mathematics education, for example working with learners’ everyday knowledge, and the languages they bring to class, are highlighted by the context of probability, enabling additional insights into the mathematical work of teaching.
Keywords: _C:Malawi MWI

EditorialAstrid T. Sinnes, William C. Kyle Jr., Busisiwe Alant, Mercy Kazima, Dorothy Nampota & Gilbert O. M. Onwu - Sinnes, Astrid; Jr, William; Alant, Busisiwe; Kazima, Mercy; Nampota, Dorothy; Onwu, Gilbert (African Journal of Research in Mathematics, Science and Technology Education, 2011)
Keywords: _C:Malawi MWI

National and local sources of power: important considerations for teacher education reforms in rural Malawi - Chazema, Jacqueline; O’Meara, James (Journal of Education for Teaching, 2011)
Keywords: _C:Malawi MWI

School Resources and Academic Performance in Sub-Saharan Africa - Lee, Valerie E.; Zuze, Tia Linda (Comparative Education Review, 2011)

Factors affecting female enrollment in basic schools in Twifo Hemang Lower Denkyira - Mfoafo, Nicholas Adu (University of Cape Coast, 2011)

What do secondary trainee teachers say about teaching as a profession of their “choice” in Malawi? - Mtika, Peter; Gates, Peter (Teaching and Teacher Education, 2011)
Keywords: _C:Malawi MWI

Exploring the Potential and Challenges of Integrating Environmental Issues in Formal Education in Malawi - Nampota, Dorothy (African Journal of Research in Mathematics, Science and Technology Education, 2011)
Keywords: _C:Malawi MWI

Young people’s transport and mobility in sub-Saharan Africa: the gendered journey to school. - Porter, Gina; Hampshire, Kate; Abane, Albert; Tanle, Augustine; Munthali, Alister; Robson, Elsbeth; Mashiri, Mac; Maponya, Goodhope; Dube, S. (Documents d’analisi geografica., 2011)
Keywords: ⛔ No DOI found

Mobility, surveillance and control of children and young people in the everyday: perspectives from sub-Saharan Africa - Porter, Gina; Hampshire, Kate; Munthali, Alister; Robson, Elsbeth (Surveillance & Society, 2011)

Disrupting patterns of educational inequality and disadvantage in Malawi - Pridmore, Pat; Jere, Catherine (Compare: A Journal of Comparative and International Education, 2011)
Keywords: _C:Malawi MWI

The role of distance teacher education in increasing the supply of primary school teachers in Sub-Saharan Africa - Sifuna, Daniel N. (Journal of International Cooperation in Education, 2011)
Keywords: _C:Malawi MWI; ⛔ No DOI found

Ensuring quality by attending to inquiry: Learner-centered pedagogy in sub-Saharan Africa - Vavrus, Frances; Thomas, Matthew; Bartlett, Lesley (UNESCO-IICBA Addis Ababa, Éthiopie, 2011)

Effective Early Literacy Instruction in Southern Malawi: Teachers' Beliefs and Consequences for Reform - Wiener, Karen Ann (Harvard University, 2011)
Keywords: _C:Malawi MWI

Age at Menarche, Schooling, and Sexual Debut in Northern Malawi - Glynn, Judith R.; Kayuni, Ndoliwe; Floyd, Sian; Banda, Emmanuel; Francis-Chizororo, Monica; Tanton, Clare; Molesworth, Anna; Hemmings, Joanne; Crampin, Amelia C.; French, Neil (PLoS ONE, 2010)
Background: Age at sexual debut is a key behavioural indicator used in HIV behavioural surveillance. Early age at menarche may precipitate early sex through perceived readiness for sex, or through school drop-out, but this is rarely studied. We investigated trends and circumstances of sexual debut in relation to schooling and age at menarche. Methods and Findings: A cross-sectional sexual behaviour survey was conducted on all individuals age 15–59 within a demographic surveillance site in Karonga District, Malawi. Time trends were assessed using birth cohorts. Survival analysis was used to estimate the median age at menarche, sexual debut and first marriage. The 25th centile was used to define ‘‘early’’ sex, and analyses of risk factors for early sex were restricted to those who had reached that age, and were done using logistic regression. Of the 8232 women and 7338 men resident in the area, 88% and 78%, respectively, were seen, and, 94% and 92% of these were interviewed. The median reported age at first sex was 17.5 for women and 18.8 for men. For women, ages at menarche, sexual debut and first marriage did not differ by birth cohort. For men, age at sexual debut and first marriage decreased slightly in later birth cohorts. For both men and women increased schooling was associated with later sexual debut and a longer delay between sexual debut and first marriage, but the associations were stronger for women. Earlier age at menarche was strongly associated with earlier sexual debut and marriage and lower schooling levels. In women early sexual debut (,16 years) was less likely in those with menarche at age 14–15 (odds ratio (OR) 0.31, 95%CI 0.26–0.36), and $16 (OR 0.04, 95%CI 0.02–0.05) compared to those with menarche at ,14. The proportion of women who completed primary school was 46% in those with menarche at ,14, 60% in those with menarche at 14–15 and 70% in those with menarche at $16. The association between age at menarche and schooling was partly explained by age at sexual debut. The association between age at menarche and early sex was not altered by adjusting for schooling. Conclusions: Women with early menarche start sex and marry early, leading to school drop-out. It is important to find ways to support those who reach menarche early to access the same opportunities as other young women.
Keywords: _C:Malawi MWI

Improving Educational Opportunities: Can Public Administrators Build a Sustainable Middle Class in Zambia? - Lentz, Corliss (Comparative Studies of South Asia, Africa and the Middle East, 2010)
Zambia has problems with its education system that inhibit the growth of an educated, middle-class workforce. While it has made dramatic progress in access to lower education in the past decade, it has had more difficulty expanding educational opportunities for grades 8–12 and in higher education. In addition to a persistently high HIV/AIDS infection rate, Zambia has a rapidly growing young population but lacks infrastructure, qualified teachers, and enough college graduates to achieve its educational goals. This article identifies the problems that threaten the educational system and makes recommendations to help Zambia achieve its goal to build a sustainable middle class.
Keywords: _C:Malawi MWI

Transition from primary to secondary education: A review of policy experiences in Malawi - Chimombo, Joseph (2010)
Keywords: _C:Malawi MWI; ⛔ No DOI found

The prospects and challenges of open learning and distance education in Malawi - Chimpololo, Andrew (International Journal of Educational and Pedagogical Sciences, 2010)
Keywords: _C:Malawi MWI; ⛔ No DOI found

Sustainability Science Education in Africa: Negotiating indigenous ways of living with nature in the third space - Glasson, George E.; Mhango, Ndalapa; Phiri, Absalom; Lanier, Marilyn (International Journal of Science Education, 2010)
Keywords: _C:Malawi MWI

Research in Ghanaian public universities: perceptions and experiences of academic staff at the University of Ghana - Gyan, George (2010)

Waves of educational model production: The case of higher education institutionalization in Malawi, 1964–2004 - Holland, Dana G. (Comparative Education Review, 2010)
Keywords: _C:Malawi MWI

Equity and Quality Issues in Mathematics Education in Malawi Schools - Kazima, Mercy; Mussa, Chikondano (Mapping Equity and Quality in Mathematics Education, 2010)
AB  - In this chapter, we discuss equity and quality of mathematics education in Malawi in terms of equal opportunities of education to all groups of learners and in terms of indicators of quality developed by the Malawi government. We focus on female and male learners and also on rural and urban schools. Differences between female and male learners include that the proportion of females is much less than that of males especially in secondary and higher education, and that female learners perform poorer than males in mathematics at all levels. Differences between rural and urban schools include access to resources where schools in urban areas have access to more and better human and material resources than rural schools, and that rural schools perform poorer than urban schools in mathematics national examinations. These differences indicate that these groups of learners do not have equal access and equal quality mathematics education. We discuss and critique some prospects for change which include commitment by government and associated initiatives and projects. Drawing on findings from some studies in Malawi, we argue that the indicators of quality as developed in Malawi focus on resources only and therefore take a simplistic view of equity.KeywordsMalawi-Mathematics education-Education access-Quality education-Equity
Keywords: _C:Malawi MWI

Household characteristics and delayed school enrollment in Malawi - Moyi, Peter (International Journal of Educational Development, 2010)
Keywords: _C:Malawi MWI

Developing learner-centred education among secondary trainee teachers in Malawi: The dilemma of appropriation and application - Mtika, Peter; Gates, Peter (International Journal of Educational Development, 2010)
Keywords: _C:Malawi MWI

Where dogs, ghosts and lions roam: learning from mobile ethnographies on the journey from school - Porter, Gina; Hampshire, Kate; Abane, Albert; Munthali, Alister; Robson, Elsbeth; Mashiri, Mac; Maponya, Goodhope (Children's Geographies, 2010)

Children as Research Collaborators: Issues and Reflections from a Mobility Study in Sub-Saharan Africa - Porter, Gina; Hampshire, Kate; Bourdillon, Michael; Robson, Elsbeth; Munthali, Alister; Abane, Albert; Mashiri, Mac (American Journal of Community Psychology, 2010)